The Characterızatıons Of Null Quaternionic Curves In Minkowski 3-Space - Özel, Şeyda; Kulahci, Mihriban Alyamac; Bektaş, Mehmet (My University, 2021)
In this study, we investigate some characterizations of Null Quaternionic curves in the Minkowski 3-space. Also,we research Null Quaternionic curves’s the characterizations in Minkowski 3-space.
Keywords: Slant helices; Null Quaternionic curves; Serret-Frenet Formulae; Helices